Ephemeris Updates For Seven Selected HATNet Survey Transiting Exoplanets - Poro, A.; Farahani, F. A.; Jahangiri, E.; Sarostad, A.; Gozarandi, M.; Haghgou, M.; Abolhassani, F.; Fakhrabadi, A.; Jongen, Y.; Wünsche, A.; Naves, R.; Guerra, P.; et al. (ՀՀ ԳԱԱ «Գիտություն» հրատ.)
We refined the ephemeris of seven transiting exoplanets HAT-P-6b, HAT-P-12b, HAT-P-18b, HAT-P-22b, HAT-P-32b, HAT-P-33b, and HAT-P-52b. We observed 11 transits from eight observatories in different filters for HAT-P-6b and HAT-P-32b. Also, the Exoplanet Transit Database (ETD) observations for each of the seven exoplanets were analyzed, and the light curves of five systems were studied using Transiting Exoplanet Survey Satellite (TESS) data. We used Exofast-v1 to simulate these ground- and space-based light curves and estimate mid-transit times. We obtained a total of 11, 175 and 67 mid-transit times for these seven exoplanets from our observations, ETD and TESS data, respectively, along with 155 mid-transit times from the literature. Then, we generated transit timing variation (TTV) diagrams for each using derived mid-transit times as well as those found in the literature. The systems' linear ephemeris was then refined and improved using the Markov Chain Monte Carlo (MCMC) method. All of the studied exoplanets, with the exception of the HAT-P-12b system, displayed an increasing trend in the orbital period in the TTV diagrams. Уточнены эфемериды семи транзитирующих экзопланет HAT-P-6b, HATP- 12b, HAT-P-18b, HAT-P-22b, HAT-P-32b, HAT-P33b и HAT-P-52b. В восьми обсерваториях наблюдено 11 транзитов в различных фильтрах для HAT-P-6b и HAT-P-32b. Также были проанализированы наблюдения базы данных транзитов экзопланет (ETD) для каждой из семи экзопланет, а кривые блеска пяти систем были исследованы с использованием данных космического телескопа TESS. Мы использовали Exofast-v1 для моделирования этих наземных и космических кривых блеска и оценки времени середины транзита. В общем получены 11, 175 и 67 времен середины транзита для этих семи экзопланет из наших наблюдений, ETD и TESS данных, соответственно, а также 155 времен середины транзита из литературы. Составлены диаграммы вариации времени транзита (TTV) для каждой из них, используя полученные времена середины транзита, а также те, которые были найдены в литературе. Затем линейные эфемериды систем были уточнены и улучшены с использованием метода Марковской цепи Монте-Карло (MCMC). Все изученные экзопланеты, за исключением системы HAT-P-12b, показали тенденцию увеличения орбитального периода на диаграммах TTV.
Keywords: Astrophysics